2012
DOI: 10.5039/agraria.v7isa2227
|View full text |Cite
|
Sign up to set email alerts
|

Influência de casca de arroz carbonizada em diferentes substratos na qualidade de mudas de tomateiro

Abstract: Com o objetivo de definir proporções de casca de arroz carbonizada em diferentes substratos na qualidade de mudas de tomateiro, realizou-se o presente trabalho. O experimento foi conduzido em delineamento inteiramente casualizado, com quatro repetições. Os 20 tratamentos foram dispostos em esquema fatorial 4x5 sendo o primeiro fator constituído de quatro substratos (PlantHort I, PlantHort II, PlantHort III e Bioplant ® ) e o segundo constituído de cinco proporções de casca de arroz carbonizada (0, 25, 50, 75 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
3
0
3
Order By: Relevance
“…S1 (100% humus), S2 (50% humus + 50% bovine manure), S3 (50% humus + 50% chicken manure), S4 (50% humus + 25% chicken manure + 25% bovine manure), S5 (50% humus + 25% chicken manure + 25% carbonized rice husk), S6 (50% humus + 25% bovine manure + 25% carbonized rice husk) and S7 (50% humus + 50% carbonized rice husk). Silva et al (2012) and Cerqueira et al (2015), when working with production of tomato seedlings of the cultivars Santa Clara and Santa Cruz, respectively, found similar values for height, stem diameter, and average number of leaves, which corroborate this study. In Table 2, the types of combinations of the substrates that were used in this study influenced the production of tomato seedlings.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…S1 (100% humus), S2 (50% humus + 50% bovine manure), S3 (50% humus + 50% chicken manure), S4 (50% humus + 25% chicken manure + 25% bovine manure), S5 (50% humus + 25% chicken manure + 25% carbonized rice husk), S6 (50% humus + 25% bovine manure + 25% carbonized rice husk) and S7 (50% humus + 50% carbonized rice husk). Silva et al (2012) and Cerqueira et al (2015), when working with production of tomato seedlings of the cultivars Santa Clara and Santa Cruz, respectively, found similar values for height, stem diameter, and average number of leaves, which corroborate this study. In Table 2, the types of combinations of the substrates that were used in this study influenced the production of tomato seedlings.…”
Section: Resultssupporting
confidence: 77%
“…Costa et al (2015) verified when working with seedlings of cherry tomatoes in different types of substrates, that the ones that contained chicken bedding were the ones that presented the highest averages in relation to the quality index of seedlings, dry and fresh matter of roots and compared to other types of substrate formulation. Silva et al (2012) evaluating the addition of carbonized rice husk on different substrates for the production of tomato cv. Santa Clara observed a quadratic reduction of shoot mass and root mass.…”
Section: Resultsmentioning
confidence: 99%
“…The seedlings produced in the SMS of A. bisporus were of higher quality because they produced a significantly greater number of leaves which affects all the future development of these plants. Silva et al (2012) observed that the seedlings produced in organic substrates had greater diameter of the colon, indicating a higher quality of the seedlings after transplanting.…”
Section: Physical Parameters Of Tomato Seedlingsmentioning
confidence: 88%
“…Thus, it is necessary to develop research to support the transition from the use of commercial (high-cost) substrates to alternative (low-cost) substrates. Silva et al (2012) recommend the use of the alternative substrate PlantHort I and the mixture of 76% PlantHort I and 24% CRH to improve the quality of tomato seedlings.…”
Section: Introductionmentioning
confidence: 99%